A method for preparing a CPVC / chlorovinyl-acetate resin blended reinforced bonding type inner support hollow fiber membrane
Patent Information
- Application Number
- CN202611197452.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0034]1、本发明将特定醋酸乙烯酯含量的二元氯醋树脂引入CPVC内支撑膜体系中,兼具加工改性和界面改性双重功能;既能有效降低铸膜液体系的整体黏度、改善熔体流动性并拓宽纺丝工艺窗口,又能借助极性酯基显著提升铸膜液与PET编织管之间的浸润性,实现分子链间的互锁锚固,从而同步提升膜体韧性与界面结合强度,突破了传统单一改性技术的局限性。
Smart Images

Figure CN122974140A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hollow fiber membrane technology for water treatment, specifically relating to a method for preparing a CPVC / vinyl chloride resin blended reinforced bonding type internally supported hollow fiber membrane. Background Technology
[0002] Internally supported hollow fiber membranes use PET hollow braided tubing as the mechanical matrix, effectively overcoming the shortcomings of traditional self-supporting hollow fiber membranes, such as low mechanical strength and susceptibility to tensile breakage. This makes them the mainstream application product in the current MBR (Membrane Bioreactor) wastewater treatment field. CPVC resin, in particular, possesses excellent acid and alkali resistance, resistance to microbial attack, and hydrolysis resistance, while also being cost-effective and exhibiting excellent film-forming properties. It is a preferred material to replace high-cost PVDF membrane materials and has extremely high industrial application value.
[0003] However, the internal support membrane prepared from pure CPVC has revealed three major technical shortcomings in actual industrial production and application: First, the strong rigidity of CPVC molecular chains and the large intermolecular forces result in high viscosity of the casting solution and poor processing fluidity. This makes it prone to problems such as spinneret clogging and uneven membrane wall thickness during spinning, resulting in a narrow overall process control window and difficulty in meeting the stability requirements of large-scale mass production. Second, pure CPVC membranes are highly brittle and have low elongation at break after formation. Under the high-intensity aeration and scouring conditions of MBRs and the harsh hydraulic shearing conditions, they are prone to cracking and fiber breakage, severely limiting their service life. Third, the weak chemical polarity of the CPVC resin surface leads to poor wettability with the PET braided tube, resulting in only a weak physical adhesion between the membrane skin and the support tube. Insufficient interfacial bonding makes the membrane skin prone to peeling, delamination, and fiber leakage during long-term operation, seriously affecting the effluent quality and the overall operational stability of the membrane module.
[0004] To overcome the aforementioned shortcomings, current industry-standard modification methods have significant limitations: On the one hand, modification using conventional additives such as chlorinated polyethylene, methyl methacrylate-butadiene-styrene terpolymer, or thermoplastic polyurethane typically only improves the toughness of the membrane, failing to simultaneously improve the processing fluidity of the casting solution and the adhesion performance of the membrane-tube interface. Furthermore, due to the poor compatibility of these additives with CPVC, additional compatibilizers are often required, leading to a complex system and a singular modification effect. On the other hand, strengthening interfacial bonding through surface treatments such as plasma treatment, silane coupling modification, or pre-coating transition layers faces practical difficulties such as cumbersome processes, high equipment investment, and low production efficiency. Moreover, a secondary interface exists between the transition layer and the skin layer, and the risk of delamination cannot be completely eliminated under long-term complex operating conditions.
[0005] Furthermore, existing vinyl chloride-vinyl acetate (PVC) resin blending technologies are mostly limited to the fields of ordinary PVC self-supporting films, coatings, and adhesives. There is currently no dedicated modification scheme for CPVC internally supported hollow fiber films, and even less so a coupled process system that can simultaneously control the casting processing performance, film mechanical toughness, and membrane-tube interface bonding performance by limiting the vinyl chloride-vinyl acetate content of the PVC resin. Therefore, how to simultaneously solve the core industry pain points of poor CPVC film processing performance, high brittleness, and easy delamination at the interface, while simplifying the production process and strictly controlling costs, remains a technical challenge that urgently needs to be addressed by those skilled in the art. Summary of the Invention
[0006] The purpose of this invention is to overcome the defects of the prior art and provide a method for preparing a CPVC / vinyl chloride resin blended reinforced adhesive internally supported hollow fiber membrane.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a CPVC / vinyl chloride resin blend reinforced adhesive internally supported hollow fiber membrane includes the following steps:
[0009] (1) Mix chlorinated polyvinyl chloride resin, chlorinated vinyl acetate resin, hydrophilic pore-forming agent and organic solvent, stir evenly at 55-65℃ and let stand to degas, to obtain casting solution;
[0010] (2) The casting solution is coated on the outer surface of the PET support tube through the spinning spinneret, and after traveling vertically downward in the air for 1-5 cm, it enters the coagulation bath to solidify and form a molded part, wherein the spinning traction speed is 10-25 m / min.
[0011] (3) The molded part obtained in step (2) is soaked and washed in pure water at 20-30°C, then soaked in a mixture of water and glycerin, and then dried in an oven at 45-50°C to obtain the CPVC / vinyl chloride resin blended reinforced bonding type internal support hollow fiber membrane.
[0012] In a preferred embodiment of the present invention, the chlorinated vinyl acetate resin is a vinyl chloride-vinyl acetate binary copolymer resin with a vinyl acetate content of 13-15 wt%; the chlorine content of the chlorinated polyvinyl chloride resin is 63-68 wt%.
[0013] In a preferred embodiment of the present invention, the organic solvent is at least one of dimethylformamide, dimethylacetamide and N-methylpyrrolidone; and the hydrophilic porogen is polyethylene glycol.
[0014] In a preferred embodiment of the present invention, the casting solution comprises the following raw materials in weight percentages:
[0015] Chlorinated polyvinyl chloride resin: 15-25 wt%
[0016] Chlorinated vinyl acetate resin: 4–7 wt%
[0017] Hydrophilic porogen: 10–20 wt%
[0018] Organic solvents: Add to 100 wt%.
[0019] More preferably, the casting solution comprises the following raw materials in weight percentages:
[0020] Chlorinated polyvinyl chloride resin: 18–22 wt%
[0021] Chlorinated vinyl acetate resin: 5-6 wt%
[0022] Hydrophilic porogen: 12–18 wt%
[0023] Organic solvents: Add to 100 wt%.
[0024] In a preferred embodiment of the present invention, the order of adding the casting solution in step (1) is as follows:
[0025] First, add the weighed organic solvent to the mixing tank, then add all of the chloroacetic acid resin and stir until completely dissolved;
[0026] Add 30% of the total mass of the hydrophilic porogen and stir until completely dissolved;
[0027] Add chlorinated polyvinyl chloride resin in batches and stir to dissolve;
[0028] Finally, add the remaining 70% of the total mass of hydrophilic porogen in batches and stir until homogeneous.
[0029] In a preferred embodiment of the present invention, in step (2), the coagulation bath is water or a mixture of water and the organic solvent, and the temperature of the coagulation bath is 70°C.
[0030] In a preferred embodiment of the present invention, in step (2), the PET support tube coated with casting solution travels vertically downward in the air for a distance of 3 to 5 cm, and the spinning traction speed is 20 to 25 m / min.
[0031] In a preferred embodiment of the present invention, in step (3), the soaking time in pure water is 24 h; the mass percentage concentration of glycerol in the mixture of water and glycerol is 40 wt%, and the soaking time in the mixture of water and glycerol is 0.1-0.5 h.
[0032] In a preferred embodiment of the present invention, in step (3), the drying time in the drying room at 45-50°C is 5-8 h.
[0033] The beneficial effects of this invention are:
[0034] 1. This invention introduces a binary vinyl acetate resin with a specific vinyl acetate content into the CPVC internal support membrane system, which has the dual functions of processing modification and interface modification. It can effectively reduce the overall viscosity of the casting solution system, improve melt flowability and broaden the spinning process window. At the same time, it can significantly improve the wettability between the casting solution and PET braided tubing by means of polar ester groups, realize the interlocking anchoring between molecular chains, and thus simultaneously improve the toughness of the membrane and the interfacial bonding strength, breaking through the limitations of traditional single modification technology.
[0035] 2. This invention eliminates the cumbersome processes of conventional industry procedures such as plasma treatment, silane coupling modification, and pre-coating transition layers. It does not require dedicated surface modification equipment and relies entirely on the material properties of the resin blend system itself to achieve interface enhancement. This not only completely eliminates secondary interface defects but also greatly simplifies the production process, improves production efficiency, and significantly reduces equipment and labor costs, making it extremely suitable for large-scale industrial mass production.
[0036] 3. The specific ratio of chloroacetic acid resin selected in this invention can moderately slow down the phase separation rate of the CPVC system and effectively suppress the coarse, interconnected finger-like pore structure that is easily generated in the pure CPVC system; thereby constructing an excellent gradient structure of "dense thin skin layer + outer sponge layer + inner finger-like pores", which comprehensively improves the retention accuracy and structural integrity of the membrane material while ensuring that the membrane material has a high pure water flux, and effectively reduces the membrane fiber defect rate and operation failure rate.
[0037] 4. The chloroacetic acid resin selected in this invention has a similar main chain structure to CPVC resin and has excellent thermodynamic compatibility. No additional compatibilizer is required, which fundamentally eliminates the risk of additive precipitation. The prepared membrane material exhibits outstanding resistance to acid and alkali, resistance to microbial erosion and aging. It can withstand the high-intensity aeration and hydraulic shear of MBR for a long time, with an extremely low flux decay rate. Its operational stability and service life are significantly better than those of traditional modified CPVC membranes. Attached Figure Description
[0038] Figure 1 This is a cross-sectional scanning electron microscope (SEM) image of the CPVC / vinyl chloride resin blend reinforced adhesive hollow fiber membrane prepared in Example 1 of the present invention.
[0039] Figure 2 This is a cross-sectional scanning electron microscope (SEM) image of the pure CPVC internally supported hollow fiber membrane prepared in Comparative Example 1. Detailed Implementation
[0040] The following embodiments will further illustrate the present invention with reference to the accompanying drawings.
[0041] Unless otherwise specified, the raw materials, reagents, and equipment used in the following embodiments and comparative examples of this invention are all commercially available products in the art. To objectively and quantitatively verify the technical advantages of the formulation and process of this invention, the samples prepared in each embodiment and comparative example were subjected to performance testing under uniform testing conditions. The testing standards and methods are as follows:
[0042] Casting solution viscosity: The dynamic viscosity of the casting solution at 60 °C was tested using a rotational viscometer;
[0043] Elongation at break: The casting solutions of each embodiment and comparative example were spun into homogeneous hollow film filaments under unsupported tube conditions, and their elongation at break was tested using a universal testing machine.
[0044] Membrane-tube interfacial bonding strength (burst pressure): The burst pressure method is used to test the interfacial peel strength between the membrane layer and the inner support tube;
[0045] Pure water flux: The pure water flux was measured using a membrane flux analyzer at 25 ℃ and a test pressure of 0.1 MPa.
[0046] Long-term operational stability: Each membrane fiber sample was made into an MBR membrane module and placed in a wastewater treatment test environment for continuous high-intensity aeration and flushing tests to examine long-term operational stability and flux decay rate.
[0047] Example 1
[0048] (1) Preparation of casting solution: 500 g of chlorovinyl acetate resin (purchased from Wuxi Honghui, model UM50, vinyl acetate content 15%) and 6500 g of organic solvent dimethylacetamide (DMAC) were added to a stirred tank and mixed. The mixture was heated to 60 °C and stirred at high speed until homogeneous. Then, 360 g of hydrophilic porogen polyethylene glycol 4000 (PEG 4000) was added to the tank and stirred until the polyethylene glycol 4000 was completely dissolved. Next, 1800 g of chlorinated polyvinyl chloride resin (CPVC, purchased from Formolon TY-CPVC, chlorine content: 65.5~67.5 wt%) was added in three batches and stirred until the CPVC was fully dissolved. Finally, the remaining 840 g of polyethylene glycol 4000 was added in batches. After the material is added, keep the system at 60 ℃ and stir at high speed until it is uniform. After stirring, let it stand for 24 h to fully remove the tiny air bubbles in the system, and a uniform and transparent casting solution will be obtained.
[0049] (2) Spinning and forming: The casting solution prepared in step (1) is uniformly coated on the outer surface of the PET hollow braided support tube through the spinning spinneret; the coated film filaments travel vertically downwards for 3 cm in the air, and then enter a pure water coagulation bath at a temperature of 70℃ to undergo phase separation and coagulation to obtain the inner support hollow fiber membrane forming part; during the spinning process, the winding wheel maintains a speed of 20 m / min for traction and winding.
[0050] (3) Post-treatment and drying: The molded part obtained in step (2) is immersed in pure water at 25 ℃ for 24 h to thoroughly remove residual solvent and pore-forming agent; after washing, it is immersed in a mixture of water and glycerin (glycerin mass fraction of 40 wt%) for 0.5 h for moisturizing treatment; after taking it out, it is placed in a drying room at 45 ℃ for 5 h to dry, thus obtaining the CPVC / vinyl chloride resin blended reinforced bonding type internal support hollow fiber membrane.
[0051] Performance test results:
[0052] The blended reinforced bonded internally supported hollow fiber membrane prepared in this embodiment has an outer diameter of 2.1 mm and an inner diameter of 0.8 mm. Its microporous structure is as follows: Figure 1 As shown, it exhibits a uniform structure consisting of a dense thin skin layer, an outer sponge-like pore layer, and an inner layer with gradient pores.
[0053] The viscosity of the casting solution at 60 ℃ is 4680 mPa·s;
[0054] The elongation at break of homogeneous hollow fiber spun with the same formula was 29.8%;
[0055] The pure water flux at 25 ℃ and 0.1 MPa is 2636 L / (m²·h);
[0056] The burst strength of the supporting membrane is 0.60 MPa;
[0057] During a 12-month continuous high-intensity aeration and flushing test, the membrane fibers were in good condition overall, with no skin delamination or fiber breakage. The pure water flux reduction rate after 12 months was only 6.2%.
[0058] Example 2
[0059] (1) Preparation of casting solution: Mix 550 g of vinyl chloride resin (purchased from Jinan Changtai, model CT-14, vinyl acetate content 14%) with 6150 g of dimethylacetamide and stir at high speed at 65 ℃ until homogeneous. First, add 450 g of polyethylene glycol 4000 and continue stirring until completely dissolved; then add 1800 g of chlorinated polyvinyl chloride (purchased from Jinling, model CPVC-R217, chlorine content: 66.3~67.0 wt%) in three batches and continue stirring until completely dissolved; finally, add the remaining 1050 g of polyethylene glycol 4000, keep stirring at 65 ℃ until homogeneous, and let stand for 24 h to remove bubbles to obtain the casting solution.
[0060] (2) Spinning and forming: The casting solution is coated onto the PET support tube through the spinning spinneret, and after traveling vertically downwards for 5 cm in the air, it enters a pure water coagulation bath at 70 ℃ to solidify and form. The speed of the traction winding wheel is kept at 25 m / min to obtain the formed part.
[0061] (3) Post-treatment and drying: The molded parts are soaked and washed in pure water at 25 ℃ for 24 h, then soaked in 40 wt% glycerol aqueous solution for 0.5 h, and finally dried in a drying room at 45 ℃ for 5 h to obtain the blended reinforced bonding type internal support hollow fiber membrane.
[0062] Performance test results:
[0063] The resulting membrane filament has an outer diameter of 2.2 mm and an inner diameter of 0.8 mm.
[0064] The viscosity of the casting solution at 60 ℃ is 5950 mPa·s;
[0065] The breaking elongation of the homogeneous membrane filaments was 32.1%;
[0066] The pure water flux at 25 ℃ and 0.1 MPa is 2732 L / (m²·h);
[0067] The burst strength of the membrane tube is 0.70 MPa;
[0068] During a 12-month continuous high-intensity aeration and scouring test, the membrane fibers showed no delamination or breakage, and the flux decline rate was only 5.8% over 12 months.
[0069] Example 3
[0070] (1) Preparation of casting solution: 600 g of vinyl chloride resin (purchased from Hanwha, model CP-430, vinyl acetate content 14-15 wt%) was mixed with 5800 g of dimethylacetamide and stirred at high speed at 55 ℃ until homogeneous. First, 540 g of polyethylene glycol 4000 was added and stirred until completely dissolved; then 1800 g of chlorinated polyvinyl chloride (purchased from Novida, model SuperCPVC-CEX01, chlorine content: 64.0-66.5 wt%) was added in three batches and stirred until dissolved; finally, the remaining 1260 g of polyethylene glycol 4000 was added, and the mixture was stirred at high speed at 55 ℃ until homogeneous and allowed to stand for 24 h to remove bubbles, thus obtaining the casting solution.
[0071] (2) Spinning and forming: The casting solution is coated on the PET support tube, and after traveling vertically downwards for 5 cm in the air, it enters a 70 ℃ water coagulation bath to solidify and form the part. The part is then wound by a winding wheel at a speed of 25 m / min to obtain the formed part.
[0072] (3) Post-treatment and drying: The molded part is soaked in pure water at 25 ℃ for 24 h, then soaked in 40 wt% glycerol aqueous solution for 0.5 h, and then dried in a drying room at 45 ℃ for 5 h to obtain a blended reinforced adhesive internal support hollow fiber membrane.
[0073] Performance test results:
[0074] The resulting membrane filament has an outer diameter of 2.2 mm and an inner diameter of 0.8 mm.
[0075] The viscosity of the casting solution at 60 ℃ is 6330 mPa·s;
[0076] The breaking elongation of the homogeneous membrane filaments was 30.6%;
[0077] The pure water flux at 25 ℃ and 0.1 MPa is 3106 L / (m²·h);
[0078] The burst strength of the supporting membrane is 0.65 MPa;
[0079] During a 12-month continuous high-intensity aeration and scouring test, the membrane fibers showed no delamination or breakage, and the flux decline rate was only 7.1% over 12 months.
[0080] Comparative Example 1 (Pure CPVC Unmodified Film)
[0081] (1) Preparation of casting solution: Mix 360 g of polyethylene glycol 4000 with 7000 g of dimethylacetamide and stir at high speed at 60°C until homogeneous. Then add 1800 g of chlorinated polyvinyl chloride (Formolon TY-CPVC, chlorine content: 65.5~67.5 wt%) in three batches and continue stirring to dissolve. Then add the remaining 840 g of polyethylene glycol 4000, keep stirring at 60°C until homogeneous, and let stand for 24 h to remove bubbles to obtain pure CPVC casting solution.
[0082] (2) Spinning and molding: The above casting solution is coated onto the PET support tube through the spinning spinneret, and after traveling vertically downwards for 3 cm in the air, it enters the water at 70 ℃ to solidify and form a molded part. The winding wheel winds the molded part at a speed of 20 m / min.
[0083] (3) Post-treatment and drying: The molded parts are immersed in pure water at 25 ℃ for 24 h, then immersed in 40 wt% glycerol aqueous solution for 0.5 h, and dried in a drying oven at 45 ℃ for 5 h to obtain pure CPVC internally supported hollow fiber membrane (structure as shown in the figure). Figure 2 (As shown).
[0084] Performance test results: The outer diameter of the obtained membrane fiber is 2.1 mm, and the inner diameter is 0.8 mm. Figure 2 As shown, the membrane without chlorinated vinyl acetate modification formed a large number of coarse, through-hole finger-like defects and had poor interfacial polarity.
[0085] The viscosity of the casting solution at 60 ℃ is as high as 8920 mPa·s;
[0086] The elongation at break of the homogeneous membrane filaments was only 8.2% (extremely poor flexibility).
[0087] At 25 ℃ and 0.1 MPa, the pure water flux is only 831 L / (m²·h);
[0088] The burst strength of the support membrane is only 0.30 MPa (low interfacial peel strength).
[0089] In the continuous high-intensity aeration and flushing test, obvious skin delamination and local peeling occurred in the third month, and the pure water flux decreased significantly by 27% after 12 months.
[0090] Comparative Example 2 (Polyethylene glycol feeding sequence not controlled)
[0091] (1) Preparation of casting solution: Mix 500 g of vinyl chloride resin (Wuxi Honghui UM50, vinyl acetate content 15%) with 6500 g of dimethylacetamide and stir at high speed at 60 ℃ until homogeneous. Then add all 1200 g of polyethylene glycol 4000 at once and continue stirring until polyethylene glycol 4000 is completely dissolved. Then add 1800 g of chlorinated polyvinyl chloride (Formolon TY-CPVC, chlorine content: 65.5~67.5 wt%) in three portions. Keep stirring at high speed at 60 ℃ until homogeneous and let stand for 24 h.
[0092] Performance test results:
[0093] After standing, the viscosity of the casting solution increased dramatically to 89,300 mPa·s, and the system exhibited severe gelation. The excessively high viscosity caused a complete loss of fluidity, making normal spinning and coating processes impossible.
[0094] Comprehensive performance comparison analysis
[0095] To more intuitively illustrate the technical advantages of the formulation and specific step-by-step feeding process of the present invention, the core performance indicators of Examples 1-3 and Comparative Examples 1-2 are summarized in Table 1 below:
[0096] Table 1 Comparison of Performance Test Data between Examples and Comparative Examples
[0097]
[0098] According to Table 1 and Appendix 1, Figure 2 Comparative analysis shows that:
[0099] Synergistic effect of resin blending: Comparing Examples 1-3 with Comparative Example 1, it can be seen that after introducing a vinyl acetate resin with a specific vinyl acetate content, the viscosity of the casting solution decreased from 8920 mPa·s to 4680-6330 mPa·s, significantly improving fluidity; the elongation at break of homogeneous membrane filaments increased dramatically from 8.2% to 29.8%-32.1%; the interfacial burst pressure increased from 0.30 MPa to 0.60-0.70 MPa (more than doubling); and the pure water flux increased by more than three times. This fully demonstrates the excellent wetting and anchoring effect and the pore structure control effect brought by the polar ester groups of vinyl acetate resin.
[0100] The criticality of the feeding sequence: Comparing Example 1 and Comparative Example 2, it is evident that if the specific feeding sequence unique to this invention—"adding a portion of the pore-forming agent in batches to dissolve CPVC, then adding the remaining pore-forming agent"—is not adopted, but instead all the pore-forming agent is added at once, severe coating gelation occurs in the system, causing the viscosity to spike to 89300 mPa·s and resulting in complete failure. This demonstrates that the feeding sequence defined in this invention makes an irreplaceable technical contribution to controlling the viscosity of the casting solution and ensuring processability.
[0101] The above description is merely a preferred embodiment of the present invention, and therefore should not be construed as limiting the scope of the present invention. All equivalent changes and modifications made in accordance with the scope of the patent and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a CPVC / vinyl chloride resin blend reinforced adhesive type internally supported hollow fiber membrane, characterized in that: Includes the following steps: (1) Mix chlorinated polyvinyl chloride resin, chlorinated vinyl acetate resin, hydrophilic pore-forming agent and organic solvent, stir evenly at 55-65℃ and let stand to degas, to obtain casting solution; (2) The casting solution is coated on the outer surface of the PET support tube through the spinning spinneret, and after traveling vertically downward in the air for 1-5 cm, it enters the coagulation bath to solidify and form a molded part, wherein the spinning traction speed is 10-25 m / min. (3) The molded part obtained in step (2) is soaked and washed in pure water at 20-30°C, then soaked in a mixture of water and glycerin, and then dried in an oven at 45-50°C to obtain the CPVC / vinyl chloride resin blended reinforced bonding type internal support hollow fiber membrane.
2. The preparation method according to claim 1, characterized in that: The chlorinated vinyl acetate resin is a vinyl chloride-vinyl acetate binary copolymer resin with a vinyl acetate content of 13-15 wt%; the chlorine content of the chlorinated polyvinyl chloride resin is 63-68 wt%.
3. The preparation method according to claim 1, characterized in that: The organic solvent is at least one of dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; the hydrophilic porogen is polyethylene glycol.
4. The preparation method according to claim 1, characterized in that: The casting solution comprises the following raw materials by mass percentage: Chlorinated polyvinyl chloride resin: 15-25 wt% Chlorinated vinyl acetate resin: 4–7 wt% Hydrophilic porogen: 10–20 wt% Organic solvents: Add to 100 wt%.
5. The preparation method according to claim 4, characterized in that: The casting solution comprises the following raw materials by mass percentage: Chlorinated polyvinyl chloride resin: 18–22 wt% Chlorinated vinyl acetate resin: 5-6 wt% Hydrophilic porogen: 12–18 wt% Organic solvents: Add to 100 wt%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The order of adding materials in the preparation of the casting solution in step (1) is as follows: First, add the weighed organic solvent to the mixing tank, then add all of the chloroacetic acid resin and stir until completely dissolved; Add 30% of the total mass of the hydrophilic porogen and stir until completely dissolved; Add chlorinated polyvinyl chloride resin in batches and stir to dissolve; Finally, add the remaining 70% of the total mass of hydrophilic porogen in batches and stir until homogeneous.
7. The preparation method according to claim 1, characterized in that: In step (2), the coagulation bath is water or a mixture of water and the organic solvent, and the temperature of the coagulation bath is 70°C.
8. The preparation method according to claim 1, characterized in that: In step (2), the PET support tube coated with casting solution travels vertically downward in the air for a distance of 3 to 5 cm, and the spinning traction speed is 20 to 25 m / min.
9. The preparation method according to claim 1, characterized in that: In step (3), the soaking time in pure water is 24 h; the mass percentage concentration of glycerol in the mixture of water and glycerol is 40 wt%, and the soaking time in the mixture of water and glycerol is 0.1-0.5 h.
10. The preparation method according to claim 1, characterized in that: In step (3), the drying time in the drying room at 45-50℃ is 5-8 hours.